The effects of heavy smoking on oxidative stress, inflammatory biomarkers, vascular dysfunction, and hematological indices - Zhikal Omar Khudhur; Shukur Wasman Smail; Harem Khdir Awla; Gasheen Bakhtiyar Ahmed; Yara Omar Khdhir; Kawa Amin; Christer Janson (Scientific Reports)
Abstract Smoking remains a major health issue worldwide, causing various diseases. This research examines the effects of heavy smoking on oxidative stress, inflammatory biomarkers, blood vascular health, and hematological parameters. A study conducted at Par Private Hospital in Erbil, Iraq, from April to May 2024 examined 104 male heavy smokers and 94 healthy male nonsmokers. Blood and biopsy samples were collected from both groups. The groups had similar age and body mass index, reducing the chances of confounding factors. Smokers showed significantly higher levels of oxidative stress markers, including malondialdehyde (p = 0.002) and nitric oxide (p = 0.002), and lower superoxide dismutase activity (p < 0.0001) compared to controls. Smokers displayed significantly elevated levels of serum endothelin-1 and interleukin-8 (p < 0.0001). Immunohistochemical analysis showed a significant rise in myeloperoxidase-positive cells and eosinophilic granule 2-positive eosinophils among smokers, indicating heightened neutrophil and eosinophil activity. Smokers showed elevated neutrophil counts in hematological analysis, while lymphocyte counts and neutrophil-to-lymphocyte ratio remained unchanged. Oxidative stress parameters, endothelin-1 levels, inflammatory biomarkers, and hematological indices are all significantly influenced by heavy smoking, reflecting systemic inflammation and vascular dysfunction. Public health initiatives are urgently required to address the harmful health consequences of smoking, as indicated by noteworthy changes in inflammation and oxidative stress biomarkers. The study offers important information on the physical effects of long-term heavy smoking, enhancing our understanding of the health hazards associated with smoking.